2011
DOI: 10.1097/shk.0b013e3181ea4476
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcal M1 Protein-Induced Lung Injury is Independent of Platelets in Mice

Abstract: Streptococcus pyogenes of the M1 serotype is frequently associated with severe streptococcal infections. M1 protein challenge can cause widespread microthrombosis, suggesting a role of platelets in streptococcal sepsis. Herein, we hypothesized that platelets may play a role in M1 protein-induced lung inflammation and injury. M1 protein was injected intravenously in C57Bl/6 mice. For platelet and neutrophil depletion, an anti-GP1bα antibody and an anti-Gr-1 antibody, respectively, were administered before M1 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
28
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 26 publications
3
28
0
Order By: Relevance
“…Moreover, several reports indicate that statin treatment inhibits pulmonary damage (39) and increases survival in murine sepsis (21,22). Indeed, we have recently shown that simvastatin is a potent inhibitor of M1 protein-triggered neutrophil recruitment and lung damage (40). Convincing data in the literature demonstrate that statins, such as simvastatin, exert pleiotropic anti-inflammatory effects, including attenuated expression of cytokines, chemokines, and adhesion molecules, as well as decreased formation of nitric oxide (10,34,36).…”
mentioning
confidence: 99%
“…Moreover, several reports indicate that statin treatment inhibits pulmonary damage (39) and increases survival in murine sepsis (21,22). Indeed, we have recently shown that simvastatin is a potent inhibitor of M1 protein-triggered neutrophil recruitment and lung damage (40). Convincing data in the literature demonstrate that statins, such as simvastatin, exert pleiotropic anti-inflammatory effects, including attenuated expression of cytokines, chemokines, and adhesion molecules, as well as decreased formation of nitric oxide (10,34,36).…”
mentioning
confidence: 99%
“…A functional role of CXC chemokines has been proposed in streptococcal infections (44), and we have demonstrated that M1 protein is a potent stimulator of CXCL1 and CXCL2 production in the lung (41). Herein, we found that inhibition of CD162 reduced M1 protein-induced formation of CXCL1 and CXCL2 in the lung.…”
Section: Discussionmentioning
confidence: 54%
“…Although M1 protein challenge is not identical to an infection with whole bacteria, M1 protein is a dominant virulence factor on S. pyogenes, and the M1 serotype of these bacteria is most frequently associated with STSS (7). Acute lung damage is a key feature in STSS, and accumulating data suggest that activation of neutrophils is a critical component in the onset of the M1 protein-provoked lung injury (7,35,37,41). Herein, we show for the first time that targeting CD162 decreases edema formation and tissue injury in the lungs of mice exposed to M1 protein, suggesting that CD162 plays a key role in regulating acute lung damage in streptococcal infections.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations